The impact of canola meal and canola seed inclusions in broiler diets - Milan Kandel; Shemil P. Macelline; Mehdi Toghyani; Peter H. Selle; Sonia Y. Liu (Poultry Science)
A total of 450 day-old straight-run Ross 308 broiler chickens were offered nine dietary regimes where canola products primarily replaced soybean meal at varying levels in iso-energetic diets with balanced amino acid profiles. Each of the nine dietary treatments was offered to ten replicate cages, with five birds per cage from 1 to 42 days post-hatch. During the starter period (1-10 d), there was no significant dietary impact on feed intake and feed conversion ratio (FCR) (P > 0.05) and transition of canola product inclusion from 0 to 50 g/kg did not influence weight gain but transition from 50 to 100 g/kg depressed weight gain by 2.17 % (317 versus 323 g/kg, P = 0.049). From 1-24, 1-35 and 1-42 days post-hatch, canola products inclusions depressed feed intake and weight gain (P > 0.05) compared to canola products-free diet. Dietary treatments did not influence FCR for 1-42 days post-hatch. Based on pair-wise comparisons diets containing the highest canola product inclusions (Treatment 9) reduced feed intake by 6.90 % (5673 vs. 5281 g/bird, P = 0.011) and body weight gain (BWG) by 7.11 % (3727 vs. 3462 g/bird, P = 0.004) compared to canola product-free diet. Negative correlations between feed intake and pellet durability index (PDI) were detected in the finisher (r = -0.887, P = 0.001) and withdrawal phases (r = -0.869, P = 0.002). Dietary treatments did not influence carcass traits (P > 0.05). Apparent metabolizable energy (AME), nitrogen retention, and AMEn were not affected by dietary treatments. However, diets with canola products exhibited a lower AME:GE ratio compared to canola-free diets (P = 0.045). There were no significant differences in apparent starch and protein digestibility coefficients in the distal jejunum and distal ileum (P > 0.05). In conclusion, since there were no significant changes in FCR and nutrient digestibility coefficients with the inclusion of canola products, it is fair to argue that depression of growth performance in broiler chicken offered diets containing high inclusion rates of canola products is likely due to a reduction in feed intake.